2005
DOI: 10.1002/ajh.20305
|View full text |Cite
|
Sign up to set email alerts
|

Immune heparin-induced thrombocytopenia can occur in patients receiving clopidogrel and aspirin

Abstract: Platelet adenosine diphosphate (ADP) receptors may play a role in potentiating platelet activation induced by IgG from patients with immune heparin-induced thrombocytopenia (HIT), as shown by previous studies using the ADP receptor antagonists AR-C66096 and ticlopidine. Consistent with these observations, we found that platelet activation by HIT sera is also significantly reduced in patients receiving clopidogrel, an ADP receptor antagonist prodrug now in wide clinical use. Despite these in vitro and ex vivo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…This limited protective effect of clopidogrel in the setting of experimental ITT is in accordance with clinical studies demonstrating incomplete protection from HIT in patients receiving both aspirin and clopidogrel. 32 Our studies may explain the limited effect of P2Y12 inhibitors in the setting of HIT/ITT. P2Y12 inhibitors affect the sustained activation of Rap1, important for stable platelet adhesion at sites of vascular injury.…”
Section: Caldag-gefi ϫ/ϫ In Immune-mediated Thrombosis 1117mentioning
confidence: 99%
“…This limited protective effect of clopidogrel in the setting of experimental ITT is in accordance with clinical studies demonstrating incomplete protection from HIT in patients receiving both aspirin and clopidogrel. 32 Our studies may explain the limited effect of P2Y12 inhibitors in the setting of HIT/ITT. P2Y12 inhibitors affect the sustained activation of Rap1, important for stable platelet adhesion at sites of vascular injury.…”
Section: Caldag-gefi ϫ/ϫ In Immune-mediated Thrombosis 1117mentioning
confidence: 99%
“…1,20 Thrombotic thrombocytopenic purpura associated with thienopyridine therapy is a rare phenomenon that typically occurs within the first 2 weeks of use and should be considered when thrombocytopenia occurs with hemolytic anemia, renal failure, and/or neurological changes. 4 The use of glycoprotein IIb/IIIa inhibitors has previously been associated with thrombocytopenia and should be suspected when platelet counts fall soon after drug initiation. 7 Pseudothrombocytopenia, a platelet artifact, occurs commonly in patients treated with glycoprotein IIb/IIIa inhibitors and may contribute to the incidence of thrombocytopenia in this population.…”
Section: Causes Of Thrombocytopeniamentioning
confidence: 99%
“…[1][2][3][4] Among patients with non-ST-segment elevation (NSTE) ACS, previous studies have observed a low (1% to 7%) incidence of acute thrombocytopenia. [5][6][7] These studies used a conservative threshold (Ͻ100ϫ10 9 /L) to define thrombocytopenia that is lower than the clinical definition of thrombocytopenia (Ͻ150ϫ10 9 /L).…”
mentioning
confidence: 99%
“…On the one hand, the clinical effect of monotherapy with acetylsalicylic acid or dipyridamole is difficult to predict [54]. On the other hand, in patients receiving dual antiplatelet therapy (clopidogrel with acetylsalicylic acid), a rapid increase in platelet count has been observed [55]. Of note, receptor GPIIb/IIIa antagonists are not recommended [56,57] as they can (extremely rarely) cause HIT.…”
Section: Progression Of Venous or Arterial Thrombosis During Heparin mentioning
confidence: 99%